The Effect of Cup Size and Diabetes Knowledge on Sweet Tea Consumption: A Quasi-Experimental Study in Indonesia - Zalfa Aisya Zakwa; Anna Undarwati (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Sugar-sweetened beverages (SSBs) are a significant source of daily sugar intake in the community, with sweet tea being the most popular type of SSB among Indonesians. At the same time, diabetes mellitus ranks third among the leading causes of death in Indonesia. Therefore, greater attention needs to be paid to factors that could potentially reduce SSB consumption, such as package size and diabetes knowledge. Studies examining size-based nudging and diabetes knowledge in relation to SSB consumption are still limited in Indonesia. This study aims to examine size-based nudging (on sweet tea packaging) and diabetes knowledge as factors influencing sweet tea consumption. A quasi-experimental design was used with an effect size of f = 0.25 (medium), α = 0.05, and a power of 0.90, calculated using G*Power 3.1 software. An online questionnaire was distributed to 184 participants, who were asked to select their preferred cup size based on images of regular and jumbo-sized sweet tea cups to simulate size-based nudging. A 23-item diabetes knowledge questionnaire was also used to measure participants’ diabetes knowledge. The results showed a significant effect (p < .001) of cup size on sweet tea consumption, indicating the influence of size-based nudging. However, diabetes knowledge was found to have an insignificant effect (p = 0.971), indicating a knowledge-behavior gap, where higher knowledge does not always lead to healthier choices. This study provides new evidence on nudging interventions for beverage consumption in developing countries, particularly Indonesia, and highlights that size-based nudging can be a practical and low-cost policy tool to help reduce sugar-sweetened beverage consumption alongside educational efforts.